A note on due-date assignment scheduling with job-dependent learning effects and convex resource allocation. Issue 7 (3rd July 2021) - Lu, Yuan-Yuan; Wang, Ting-Ting; Wang, Rui-Qi; Li, Yang
Abstract : This note revisits single machine due-date assignment scheduling with job-dependent learning effects and resource allocation. Under the convex decreasing resource consumption function, the problem is to minimize the scheduling cost subject to a constraint on the total weighted resource consumption cost. Firstly, it is shown that the published results are incorrect by a counter-example from the literature. Then the corrected results are provided, and it is shown that this problem can be solved in polynomial time.